Leadership and Innovation Management: Driving Performance through Agility and Resilience in Automotive Enterprises - LIU, Pengxuan; PHAWITPIRIYAKLITI, Chaithanaskorn; TERASON, Sid (Journal of Ecohumanism, 2024)
The study investigates how leadership and innovation management influence organizational performance, with agility and resilience as mediating factors. The primary objective was to examine the direct and indirect effects of these variables on organizational performance. The findings show that leadership and innovation management have significant direct impacts on performance. Agility and resilience also play crucial roles in mediating these relationships, further enhancing organizational performance. The study concludes that leadership and innovation not only directly improve organizational performance but also indirectly enhance it by fostering agility and resilience, enabling organizations to adapt quickly and recover from challenges. These findings have practical implications for leaders aiming to improve long-term organizational performance and competitiveness in dynamic environments, particularly those characterized by rapid change and uncertainty. The study involved 420 human participants from various industries, representing different leadership and operational roles. A cross-sectional design was employed, and data were gathered using standardized questionnaires, including the Multifactor Leadership Questionnaire (MLQ) for leadership, and validated scales for innovation management, agility, resilience, and organizational performance. Data collection included surveys administered to participants and some secondary data to contextualize the findings. Overall, the study emphasizes the importance of fostering leadership and innovation to build agility and resilience, ensuring that organizations remain competitive and capable of sustaining high performance in fast-evolving industries. Additionally, it highlights the need for strategic focus on adaptability and operational flexibility as key drivers of long-term success.